CARDIOONCOLOGY: CHEMOTHERAPY DRUGS AND RADIATION THERAPY IMPACT ON CARDIOVASCULAR SYSTEM - D P Doundoua; A V Staferov; A V Sorokin; A G Kedrova (Клиническая практика, 2016)
Anticancer therapy can cause angina pectoris, acute coronary syndrome, stroke, critical limb ischemia, arterial hypertension, arrhythmias and heart failure. The new specialization in cardiology, called cardiooncology, exploring the complications of cardiovascular system, arising during the treatment of cancer. The first part of the review, based on the publications of the last decades, is dedicated to the definition of cardiooncology, mechanisms of cardiac and vascular toxicity with a number of anticancer drugs affecting the cardiovascular system.